Responsibilities Of The Board Of Directors In Management Of Regionally-Owned Enterprises - Nodi, Hamzar (Inspiring Law Journal, 2024)
The regional government has the function and responsibility to improve people's welfare by implementing development in all fields. The source of PAD is a source of regional finance that is excavated in the relevant region, which can come from regional taxes and regional levies. So that PAD can become part of the largest source of finance for the implementation of regional autonomy. One of the important organs in a company is the board of directors. The board of directors who control the company in its daily activities has the authority to determine policies in exercising its powers and obligations in managing the company must have good intentions, be responsible, have integrity, be honest, and be highly dedicated to advancing and developing the company. The board of directors is fully responsible personally for the company's losses if the person concerned is guilty or negligent in carrying out his duties. The board of directors can take or take actions to facilitate his duties as long as it is within the scope of his duties and obligations and does not conflict with customs, fairness, and propriety